Improved performance of Atlantic cod (Gadus morhua L.) larvae following enhancement of live feed using a fish protein hydrolysate. (26th December 2013) - Johannsdottir, J.; Heimisdottir, H.L.; Hakonardottir, K.; Hrolfsdottir, L.; Steinarsson, A.; Imsland, A.K.; Thorarensen, H.; Bergsson, A.B.; Bjornsdottir, R.
Abstract High larval mortalities and anatomical deformities are among the major obstacles restricting the development of Atlantic cod (Gadus morhua) aquaculture. The immune system of cod larvae is poorly developed at hatch, and innate immune parameters are therefore of importance for defence against environmental microorganisms. Two separate experiments were conducted with bioencapsulation of the live feed of cod larvae using a pollock (Pollachius virens) protein hydrolysate. Offering peptide enhanced live feed to larvae during the first weeks of exogenous feeding promoted larval development, with reduced incidence of severe deformities to 3.0% as compared with 9.6% deformities observed in the control group at 160 days posthatch. The production and distribution of IgM and lysozyme were furthermore increased in larvae fed peptide enhanced feed compared with control larvae. IgM was predominantly detected in the foregut and the epithelial lining of the digestive tract as well as in the epidermal mucus of the skin. Lysozyme was mainly detected in the epidermal mucus of the skin and in the foregut. Overall, the results indicate that live feed enhancement using a protein hydrolysate derived from pollock may reduce deformities and promote normal development during early production stages of cod larvae.